Regulation of STAT3 phosphorylation in cells infected with coronavirus. - Sharhana Yusof. (2011)
Acute phase response is one of the many strategies which are involved in the host cells’ anti-viral innate immunity defense. Hence, it is of interest to elucidate possible signaling pathways which take part in this response. The pathway which was looked at involves the expression of IL-6 which eventually, signals through the Janus (Jak)/ signal transducer and activator of transcription (STAT)-3. The role of STAT3 in response to infectious bronchitis virus (IBV) in different human cell lines was investigated in this study. Mock-infected and IBV-infected cells were investigated in a time-course infection manner and the phosphorylation status of STAT3 was monitored. It was found that despite there being an increase in the expression of IL-6 mRNA level, a decline in its protein level was observed. Also, initial IBV infection resulted in phosphorylation of the tyrosine (Tyr)-705 residue of STAT3. However, in later stages of infection, dephosphorylation of Tyr705 residue was seen, even with the activation of its upstream kinase, Jak2. We concluded that in an IBV infection, the Jak/STAT3 pathway is activated and that there may be some mechanisms involved in neutralizing this activation.